Partial absence of PD‐1 expression by tumor‐infiltrating EBV‐specific CD8+ T cells in EBV‐driven lymphoepithelioma‐like carcinoma. Issue 9 (9th September 2020) - Simoni, Yannick; Becht, Etienne; Li, Shamin; Loh, Chiew Yee; Yeong, Joe Poh Sheng; Lim, Tony Kiat Hon; Takano, Angela; Tan, Daniel Shao Weng; Newell, Evan W
Abstract: Objectives: Lymphoepithelioma‐like carcinoma (LELC) is an uncommon lung cancer, typically observed in young, non‐smoking Asian populations. LELC is associated with Epstein–Barr virus (EBV) infection of lung tumor cells of epithelial origin, suggesting a carcinogenic role of EBV as observed in nasopharyngeal carcinoma (NPC). Here, we studied the antigen specificity and phenotype of EBV‐specific CD8 + T cells in blood and tumor of one LELC patient positive for EBV infection in lung tumor cells. Methods: Using multiplex MHC class I tetramers, mass cytometry and mRNA sequencing, we studied EBV‐specific CD8 + T cells at the transcriptomic and phenotypic levels in blood and tumor tissues of the LELC patient. Results: Lymphoepithelioma‐like carcinoma lung tumor cells were positive for EBV infection. In both blood and tumor tissues, we detected two populations of EBV‐specific CD8 + T cells targeting the EBV lytic cycle proteins: BRLF1 and BMLF1. Transcriptomic analyses of these two populations in the tumor, which can be considered as tumor‐specific, revealed their distinct exhausted profile and polyclonal TCR repertoire. High‐dimensional phenotypical analysis revealed the distinct phenotype of these cells between blood and tumor tissues. In tumor tissue, EBV‐specific CD8 + TILs were phenotypically heterogeneous, but consistently expressed CD39. Unexpectedly, although the LELC tumor cells expressed abundant PD‐L1, these tumor‐specific CD8 + tumor‐infiltrating lymphocytes (TILs) mostly did not express PD‐1. Conclusion: Epstein–Barr virus‐specific CD8 + TILs in EBV‐driven tumor are heterogeneous and partially lack PD‐1 expression, suggesting that anti‐PD1/PD‐L1 immunotherapy may not be an appropriate strategy for disinhibiting EBV‐specific cells in the treatment of LELC patients. Abstract : We studied the antigen specificity and phenotype of CD8 + tumor‐infiltrating lymphocytes (TILs) in one LELC patient positive for EBV infection in lung tumor cells. Transcriptomic analyses of EBV‐specific CD8 + TILs reveal their distinct exhausted profiles and polyclonal TCR repertoire. Although the LELC tumor cells expressed abundant PD‐L1, EBV‐specific CD8 + TILs mostly did not express PD‐1, but express CD39.